Hubungan Asupan Makronutrien dan Aktivitas Fisik terhadap Kelebihan Gizi pada Siswa Kelas 5 di Sekolah Dasar Negeri Banjarbendo: The Correlation between Macronutrient Intake and Physical Activity with Overnutrition among Fifth-Grade Students at Banjarbendo State Elementary - Mujayanto, Mujayanto; Pratiwi, Echa Rahmalia (Universitas Airlangga, 2024)
Background: Overweight status, which falls under the category of overweight and obesity, has become a serious and growing global health problem, especially among school-aged children. Unbalanced nutrition and low physical activity are the main factors contributing to the increasing prevalence of malnutrition among children in Indonesia. Objectives: This study aims to analyze the correlation between macronutrient intake and physical activity with nutritional status (overweight and obesity) in fifth-grade students at Banjarbendo State Elementary School, Sidoarjo. Methods: This study employed an observational analytical method with a cross-sectional design. The sample consisted of 64 fifth-grade students who were randomly selected through simple random sampling. Data were collected through anthropometric measurements to determine nutritional status based on body mass index-for-age (BMI-for-age) as well as interviews to assess food intake using a 2x24 hour food recall and physical activity using a 2x24 hour physical activity recall. Data analysis was carried out using Spearman’s correlation test with a 95% confidence level (α=0.05). Results: The results indicated a significant correlation between macronutrient intake, physical activity, and nutritional status. Most students with excessive macronutrient intake and low physical activity were found to be overweight or obese Conclusions: A significant correlation between macronutrient intake, physical activity level, and nutritional status was observed. It is important to raise awareness of balanced nutrition and encourage physical activity in children to prevent overnutrition and its associated health problems in the future.